2018
DOI: 10.3758/s13420-018-0318-1
|View full text |Cite
|
Sign up to set email alerts
|

Attention toward contexts modulates context-specificity of behavior in human predictive learning: Evidence from the n-back task

Abstract: According to the attentional theory of context processing (ATCP), learning becomes context specific when acquired under conditions that promote attention toward contextual stimuli regardless of whether attention deployment is guided by learning experience or by other factors unrelated to learning. In one experiment with humans, we investigated whether performance in a predictive learning task can be brought under contextual control by means of a secondary task that was unrelated to predictive learning, but sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Thus, a crucial factor is the amount of attention dedicated to context stimuli, which again might be influenced by specific context characteristics. Correspondingly, attention to a context was found to modulate context-specificity of behavior (Uengoer et al, 2018). Relevant contexts received more attention (in terms of gaze duration), which led to more context-specific learning of humans in a behavioral predictive learning task (Lucke et al, 2013(Lucke et al, , 2014.…”
Section: Introductionmentioning
confidence: 93%
“…Thus, a crucial factor is the amount of attention dedicated to context stimuli, which again might be influenced by specific context characteristics. Correspondingly, attention to a context was found to modulate context-specificity of behavior (Uengoer et al, 2018). Relevant contexts received more attention (in terms of gaze duration), which led to more context-specific learning of humans in a behavioral predictive learning task (Lucke et al, 2013(Lucke et al, , 2014.…”
Section: Introductionmentioning
confidence: 93%
“…These results agree with the idea raised by Rosas et al (2006; Ogallar et al, 2017; Rosas & Callejas-Aguilera, 2006, 2007; see also Gawronski, Rydell, Vervliet, & De Houwer, 2010, for a related explanation in evaluative learning) that context-switch effects depend on the attention contexts receive during training, rather than on specific features of the information (cf., Bouton, 1993, 1994; Nelson, 2002, 2009), and that this attention may be modulated by the subjective relevance of the context. Subjective relevance of contextual features has been modulated by manipulating the informative value of the contexts, both in humans (e.g., León et al, 2010b, 2012; Lucke et al, 2013, 2014; see also Uengoer et al, 2018) and nonhuman animals (Preston et al, 1986). This study shows that subjective relevance of the context in human beings may be modulated by instructions.…”
Section: Discussionmentioning
confidence: 99%
“…Context subjective relevance is assumed to be modulated by the actual informative value of the context (e.g., León, Abad, & Rosas, 2008; León, Abad, & Rosas, 2010b; León, Gámez, & Rosas, 2012; Lucke, Lachnit, Koenig, & Uengoer, 2013; Lucke, Lachnit, Stüttgen, & Uengoer, 2014; Preston, Dickinson, & Mackintosh, 1986) by the relative salience of contexts and cues (e.g., Abad, Ramos-Álvarez, & Rosas, 2009; Moreno-Fernández, Abad, Ramos-Álvarez, & Rosas, 2011, see also Bouton & Sunsay, 2001), by previous experience that makes context features relevant or irrelevant within a different task (Uengoer, Lucke, & Lachnit, 2018; see also Uengoer, Pearce, Lachnit, & Koenig, 2018), and by instructions that lead human participants to attend or to ignore the context (e.g., Cañadas, Rodríguez-Bailón, Milliken, & Lupiáñez, 2013; Eich, 1985; Mertens & De Houwer, 2016; but see Neumann, 2007).…”
mentioning
confidence: 99%
“…Studies of human associative learning have revealed that response recovery after extinction is weaker when initial acquisition (Lucke et al, 2013) or extinction (Lucke et al, 2014) was conducted in a context that had been trained as being irrelevant for other stimulus-outcome relationships, compared with a context trained as being relevant. Measures of eye-gaze behavior (Lucke et al, 2013) and other experimental approaches (Uengoer et al, 2018) suggest that the impact of context information on context-dependent learning is based on processes of selective attention.…”
Section: Extinction and The Role Of Contextmentioning
confidence: 99%